Contribuição para a gestão da integração no processo de desenvolvimento de produto. - Carvalho, José Luiz Moreira de (Universidade Federal de São Carlos, 2006)
Continuous development of new and improved products is seen as a key factor for business survival and growth. A new product that satisfies consumer s needs in an efficient and opportune manner increases competitive advantage. New product development (NPD) process has a multidisciplinary and multifunctional character, demanding specialized kinds of technical knowledge, peculiar of different disciplines or functions. A successful NPD requests a good integration among these functions, so that an auxiliary tool that helps this integration can increase project s performance and, consequently, competitive performance. In this thesis an auxiliary tool for managing functional integration in new product development processes is proposed, based in three conditional factors (Context, Technological Positioning, Competences) and three dimensions (Communication, Coordination and Collaboration). The tool s proposal includes a discussion about these conditional factors and dimensions, describing how they can be used to acquire an adequate functional integration in new product development process. As a secondary contribution of the thesis, a discussion about a particular case of integration, the one between applied research and NPD project, is made, including a theoretical discussion and case studies.
Keywords: Desenvolvimento de novos produtos; Integração multifuncional; Pesquisa e desenvolvimento; Gestão da inovação; Product development; Integration; Transfunctional integration; Research & Development; New product development management; Innovation management; Applied research; ENGENHARIAS::ENGENHARIA DE PRODUCAO